Titanium mesh associated with rhBMP-2 in alveolar ridge reconstruction - Trento, G. S. [UNESP]; Carvalho, P. H.A. [UNESP]; Macedo, D. V. [UNESP]; Gabrielli, M. A.C. [UNESP]; Monnazzi, M. S. [UNESP]; Pereira-Filho, V. A. [UNESP] (Elsevier, 2019)
A systematic review of the literature was performed regarding the use of titanium mesh in association with recombinant human bone morphogenetic protein (rhBMP) for alveolar ridge reconstruction. The PubMed, Scopus, and Cochrane databases were searched for articles in English published up until June 2017. The inclusion criteria encompassed studies in humans − randomized clinical trials, prospective and retrospective studies, and case series. The screening and selection process was performed by three independent reviewers, with verification by a senior researcher in the case of disagreement. The initial search identified 92 studies. After removal of duplicates, 70 remained for title and abstract reading. Fifty-four articles were considered non-relevant, resulting in a total of 16 studies. Following application of the inclusion criteria, 10 studies were selected. An additional study was added after the hand search, giving a total of 11 articles. These reported on 106 patients who had undergone alveolar ridge augmentation with rhBMP and titanium mesh. There were 74 maxillary grafts and 22 mandibular grafts, and the success rate of rehabilitation was 93.4% to 100%. The most frequently reported complications were suture dehiscence and mesh exposure, but without graft loss. rhBMP associated with titanium mesh is a viable method for alveolar reconstruction with high success rates and low rates of local complications.
Keywords: alveolar bone grafting; alveolar bone loss; bone morphogenetic protein 2; surgical mesh